Reintroduction of ventilation components for terrace houses in Malaysia - 608338 Ismail Said; Raja Nafida Raja Shahminan; Rajeh Salleh; International Symposium on Asia Pacific Architecture (3rd : 1999 : Honolulu, Hawai'i)
03